Film-live Atlante: exploring a new qualitative methodology for a "more- than-visual" criminology - Natali, Lorenzo (Criminological encounters, 2023)
This contribution explores the expansion of the criminological imagination through creative methodologies, specifically "poetically informed" research. The focus is on a sensory and affective methodology termed "film-live," which emerges from the collaboration between a criminologist and a film director. Film-live is characterized by broadcasting a short film in a sequence shot as it is being filmed, enabling spectators to experience real-time unfolding social processes. The method emphasizes the encounter between the imaginary and the real, involving both academic and non-academic audiences in qualitative research outcomes. Drawing on symbolic, radical, critical, and cultural interactionism as the theoretical frameworks, the paper describes and discusses a pilot study, examining the method’s potential and limitations based on an experiment conducted in 2010 at Brera Fine Arts Academy, Milan (Italy).